Land-Based Employment Agencies as Modern Brokers: A Study on the Recruitment Strategies for Overseas Filipino Workers - Iwayama, Minami (Social Sciences and Development Review, 2022)
This study is focused on identifying the recruitment practices of land-based employment agencies in the Philippines. It employed a qualitative research design, particularly the case study approach. Data collection techniques include key-informant interviews and in-depth interviews, with a total of 30 participants selected through chain referral sampling. Results showed three general types of recruitment strategies, namely: (1) Applicant initiated recruitment strategy; (2) Employment agency-initiated recruitment strategy; and (3) Government initiated recruitment strategy. For the applicant-initiated recruitment strategy, walk-in was the only identified recruitment practice. For the employment agency-initiated recruitment strategies, the common recruitment practices were computer mediated recruitment, print-related recruitment, location-based recruitment, and referral-dependent recruitment. Lastly, for the government initiated recruitment strategy, job fair was the common recruitment practice. The best utilized and least effective methods of recruitment by employment agencies for each worker category recruited were identified and discussed.